Organisasi Sekolah di Masa Pandemi - Nurochim Nurochim; Siti Ngaisah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2020)
The purpose of this study is to find a picture of how the condition of the school organization during the pandemic, from the scope of individuals, social groups, relationships between organizations, relationships between institutions, and policies. The subjects of this study are literature, literature sources that discuss pandemics, conditions, individual attitudes in school organizations, relationships with social groups, communities, institutions and policies. The results of this study explain that in order for schools to continue to achieve educational goals with good quality, the integration of functions between school principals, teachers, and all school resources, groups of educators and education staff organizations, between organizations, institutions in society, and policies must work. in harmony. Conclusion, Keywords: Pandemic, School, Organization, Ecology, Social.